Production performance of four lines of Japanese quail reared under tropical climatic conditions of Tamil Nadu, India - Arunrao, Keche Vishal; Kannan, Duraisamy; Amutha, Ramasamy; Thiruvenkadan, Aranganoor Kannan; Yakubu, Abdulmojeed (Frontiers in Genetics, 2023)
This research investigated the growth and other production traits of four distinct lines (L1, L2, L3, and L4) of Japanese quail (Cortunix japanoica) kept in the tropical climate of Tamil Nadu, India. The traits related to body weight at different weeks and weight gain were measured in 180 birds (90 males and 90 females) per line up to the fifth week of age, and then 90 birds (females only) from the sixth to the 16th week of age, with egg production and feed efficiency parameters measured in 10 observations per line. The traits were analysed using the General Linear Model procedure, and Tukey’s HSD was used to test for statistical differences (p < 0.05) between the means for subclasses under a specific effect. The results revealed a highly significant difference (p < 0.01) in body weight from hatch to fifth week of age. At 5th week of age, the L3 and L2 did not differ (p > 0.05) based on Tukey test; therefore, both presented the highest values and were statistically significant (p < 0.01) with L4 with a lowest value of 203.62 g. The cumulative fifth week feed conversion ratio showed non-significant difference (p > 0.05) at first and second week, and highly significant difference (p < 0.01) from third to fifth week of age. The age at 50 per cent egg production was 60.2 (L4), 61.4 (L2), 65.1 (L3) and 66.0 (L1) days and the L1 egg production differed significantly (p < 0.01) from L4 line. The highest bodyweight (g) during the laying period (at 15 weeks of age) was observed in L2 (327.08) and L3 (326.54) and differed significantly (p < 0.01) from L1 (309.24) as well as L4 (288.69) lines. The mean egg weight (g) of different lines showed non-significant difference (p > 0.05) at all weeks, except at 11th week of age (p < 0.01). The mean feed consumption (g)/bird/day differed significantly (p < 0.01) from 6th to 16th week of age, except at sixth and eighth week of age, where it was non-significant (p > 0.05). The overall feed efficiency/dozen of eggs (from 6th to 16th weeks) ranged from 1.33 (L1) to 1.98 (L3). The livability from 6 to 16 weeks of age was 100 per cent in all the lines. In order to boost Japanese quail production in the tropics, L3 and L4 may be selected for body weight and egg production, respectively.